Estereotipos y morfología de género en nombres de rol: un estudio psicolingüístico - Stetie, Noelia Ayelén (2023)
There are few studies in Spanish that analyze the complex relationships between gender stereotypes and gender morphology, even fewer that include non-binary forms. We evaluated the effects of two independent variables (stereotype bias and gender morphology) on the comprehension of sentences that include role nouns with masculine and feminine stereotypicality. We analyzed two dependent variables: noun phrase reading time (determiner + role noun) and total reading time. We found an early incidence of stereotypes during comprehension and different effects at the noun phrase level compared to the sentence level. Furthermore, the non-binary form [-e] seemed to function as a generic term for speakers of Argentine Spanish.